(3WHbGJ GdTGaYjIs - (3ESeGYjd Hf YeQ Hf cKjQ Hf Vqh Hf OQY GdbQTj GdHUQhj Ke GdOeTbqj, CHh GdaOGA, YeGO GdOjf,J (B774 (3g` s
(3ChdgG (B:s
(3hHYO, abO JWGHbJ OdGdI GdcJGH hGdSfIYdi TQa GdYde haVdg hdeG cGf GdEeGe GdTGaYi ef CYXege bOQG CMHHJ Cf CPcQ TjFkGef CMhGdg s
(3BNQgG (B:s
(3hGMaXhG CjGe OhdJce EfgGefce Ydi NWQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B320 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B283s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B272 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs